Ragione, desiderio, artificio Hegel e Hobbes a confronto - Frilli, Guido (Premio Ricerca «Città di Firenze», 2017)
What is desire? What are the powers of reason? What drives men to go beyond nature? Where to look for the foundations and fundamental forms of coexistence? Following the thread of these questions, the study aims to set up a theoretical comparison between Hegel and Hobbes, in the belief that an all-out dialogue between the two philosophers can contribute to a better understanding of their respective systems. The examination of the many affinities of problematic approach, as well as of the radical divergences of the solutions, allows the profile of a self-critical modernity to emerge, sensitive to the assumptions of the project of human self-affirmation through reason and artifice.